Autonomic Functioning among Cocaine-Exposed Kindergarten-Aged Children: Examination of Child Sex and Caregiving Environmental Risk as Potential Moderators - Schuetze, Pamela (Neurotoxicol Teratol, 2020)
The purpose of this study was to examine the hypothesis that child sex moderates the association between prenatal cocaine exposure (PCE) and autonomic functioning as well as to examine the role that caregiving environmental risk playes in sex differences in autonomic functioning among exposed children. Measures of the parasympathetic nervous system (indexed by respiratory sinus arrhythmia [RSA]) and the sympathetic nervous system (indexed by skin conductance level [SCL]) were obtained from 146 (75 cocaine-exposed, 38 male; and 71 nonexposed, 36 male) children during baseline and a task designed to elicit negative affect (NA). We also examined the role of caregiving environmental risk as a moderator of the association between PCE and autonomic functioning separately for boys and girls. PCE boys had a significantly higher baseline RSA and lower baseline SCL than PCE girls or nonexposed children. Environmental risk also moderated the association between PCE and baseline RSA for boys, but not girls, such that boys with PCE and high environmental risk had the highest baseline RSA. These findings indicate that exposed boys had significantly lower levels of sympathetic activation while at rest. However, for autonomic reactivity, the exposed girls had a larger change in both RSA and SCL relative to nonexposed girls while exposed boys had significantly smaller increases in SCL during environmental challenge. Finally, girls with both PCE and high environmental risk had the highest levels of parasympathetic reactivity during challenge. These results underscore the importance of examining sex differences and considering comorbid environmental risk factors when examining developmental outcomes in cocaine-exposed children and highlight the complexity involved with understanding individual differences in cocaine-exposed populations.